Criteria For The Use Of Abandoned Limestone And Gypsum Quarries For Sanitary Landfill Sites In Iowa ? Introduction - Donivan L. Gordon (Society for Mining, Metallurgy & Exploration, 1974)
One of the several problems facing society today is that of disposing of its solid waste. Each year this nation spends approximately 4.5 billion dollars to collect, transport and dispose of some 360 million tons of domestic and industrial solid waste. Although considerable sums of time and money have been spent in researching various techniques for solid waste disposal, it is presently agreed that sanitary landfilling represents the most economic and universally adaptable solution to the problem of solid waste disposal. However, regardless of the factors favoring sanitary landfilling as the waste disposal method of choice, it should be recognized as carrying with it a potential for the degradation of ground- and surfacewater resources. Through an interdisciplinary effort regulations were promulgated during 1971 in the State of Iowa to govern sanitary disposal projects. Consistent with a set of rationales developed to preserve environmental quality, these regulations set forth hydrologic and geologic standards designed to protect Iowa's water resources. Minimum requirements have been outlined in the regulations through which the natural favorability of potential landfill sites may be evaluated. Natural favorability is primarily defined in terms of the hydrologic and geologic relationships between a proposed landfill site and those in the locality of the site. The regulations specify that leakage from a landfill to a subcropping aquifer must be less than 0.04 cu ft/day/sq ft at the base of the landfill. This factor is offered to quantify the maximum allowable leakage for all sites in unconsolidated sequences underlain by subcropping bedrock aquifers, Based on groundwater research in Iowa, the assumption is made that 50 feet of till will be sufficient to inhibit the downward flow of liquids from a landfill into bedrock aquifers. This assumes a difference of no greater than 40 feet in hydrostatic head between the water table in the unconsolidated sequence and that in the bedrock aquifer. Owing to the fact that bedrock aquifers in many areas of the state are mantled by less than 50 feet of till the regulations provide for site modification, through engineering, to meet the specified leakage standard, In such instances the leakage factor is evaluated by means of the generalized Darcy's Law Q = PIA where: